Recent advances on gold and silver nanoparticle-based colorimetric strategies for the detection of different substances and SARS-CoV-2: a comprehensive review. Issue 10 (16th August 2022) - Sahu, Sushama; Sharma, Srishti; Kurrey, Ramsingh; Ghosh, Kallol K.
Abstract : Nanoparticle (NP)-based colorimetric methods are extensively used for the rapid detection of different substances and SARS-CoV-2 in various fields such as environmental science, virology, pollution research, food industry, as well as biomedicine. Abstract : Nanoparticle (NP)-based colorimetric methods are extensively used for the rapid detection of environmental contaminants, different substances and SARS-CoV-2 in various fields such as environmental science, virology, pollution research, and the food industry, as well as biomedicine. Colorimetric sensors exhibit high sensitivity and selectivity, are easy to handle, portable, safe for screening purposes and can be visualized by the naked eye. Herein, the colorimetric sensing approaches of the two most commonly used metallic NPs, i.e., gold (Au) and silver (Ag), and their physicochemical methods are discussed, as metallic NPs show good efficiency due to their unique optical and chemical properties. This review summarizes the progress on colorimetric sensors based on metallic NPs as sensors and their applications, elucidating the utility and superior features of metallic-NP-based colorimetric assay for the detection of different environmental contaminants, biomolecules and SARS-CoV-2 in the environmental as well as human biological samples. An outlook with respect to the trends and future development of the proposed sensors is also provided.